Configurations of the real in Chinese literary and aesthetic modernity - Button, Peter (Leiden ; Boston : Brill, 2009)
"Tracing the formation of the modern concept of literature in 20th century China, this book examines the emergence of the Chinese socialist realist novel in relation to the literary and philosophical currents globalized in the wake of capitalist modernity"--Provided by publisher.
The trials of Chinese literary realism -- Lu Xun's Ah Q as gruesome hybrid -- The aesthetic critique of modernity in Chinese Marxism, new criticism, and Adorno -- Global/modern figurations of the type in Cai Yi, Heidegger, and Whitman -- Aesthetics and desire in Yang Mo's Song of youth.
Bibliografija: str. [289]-299 i kazalo.
Keywords: kineska književnost - proza -- kineska književnost - 20 st. -- teorija književnosti; socijalrealizam u književnosti